Implementasi Bimbingan Dan Konseling Spiritual Dalam Mengatasi Perilaku Menyimpang Siswa SMKN Tengaran - Aisyahri, Tya; Ningtyas, Regina Dwi Cahya; Nugroho, Muhammad Aji (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2025)
Deviant behavior among vocational high school students often arises from complex factors, including identity crises, emotional instability, and a sense of spiritual emptiness. These conditions indicate that interventions aimed at addressing student misconduct should not be limited to cognitive, behavioral, or socio-cultural approaches alone, but must also consider the spiritual dimension as an integral aspect of human development. From an Islamic perspective, humans are not merely psychological and social beings but are also creatures of Allah SWT who require guidance rooted in faith, moral values, and inner peace. Therefore, the implementation of guidance and counseling services in educational institutions needs to adopt a holistic framework that integrates spiritual values alongside conventional counseling principles. This study aims to describe the implementation of spiritually-based Guidance and Counseling (BK) in addressing various forms of deviant behavior among students at SMKN Tengaran. The research employs a descriptive qualitative approach with a literature-based design. Data were collected through in-depth interviews with guidance and counseling teachers, students who participated in counseling services, and direct observations of guidance and counseling practices conducted at the school. The collected data were analyzed to identify patterns, strategies, and outcomes related to the application of spiritually-oriented counseling. The findings reveal that spiritually-based Guidance and Counseling plays a significant role in helping students internalize positive moral and religious values, develop self-awareness, and strengthen their spiritual resilience. This approach encourages students to reflect on their behavior, enhance their relationship with Allah SWT, and foster a sense of responsibility toward themselves and their social environment. Overall, spiritually-based counseling emerges as a relevant and effective intervention model for vocational high school students, offering a comprehensive solution to deviant behavior by addressing both external actions and internal spiritual conditions